Framework of affordable cooperative housing through an innovative waqf-based source of finance in Karachi - Khan, Muhammad Kashif; Abdul Rasid, Siti Zaleha; Bardai, Barjoyai; Saruchi, Sarah Athirah (Emerald Insight, 2022)
Purpose – The purpose of this research is to introduce an innovative framework called the waqf cooperative housing framework (WCHF), with an objective to create a synergistic equilibrium between waqf and cooperative housing schemes. To tackle problems related to the dearth of financing, this research postulates an innovative waqfbased source of finance that involves generating revenue from common areas (waqf area) within the vicinity of the condominium. Design/methodology/approach – Primary data were collected through interviews and the data were analysed using the NVIVO software. The interviewees comprised managers from property development sectors, public sector officials, university lecturers in Islamic finance, CEOs, top management officials from Islamic financial institutions, community leaders and shariah scholars. Findings – A framework was proposed based on the result of the interviews. It was found that innovative models such as WCHF can resolve the issue of affordable housing in Karachi such as decreasing the financial burden on the public exchequer, bringing positive change to the lives of the poor, fulfilling the property developer’s corporate social responsibility, fulfilling the religious duty of the general public and condominium owners towards their fellow beings as well as creating new employment opportunities for people who are working in the financial sector (waqf management companies/trustees) and the construction sector. Research limitations/implications – Even though this study has introduced an innovative and practical solution to the financing of affordable housing, it also encountered some limitations. First, it is conducted in Karachi city involving six group of respondents; thus, the findings cannot be generalised with other contexts. Similar research needs to be conducted in different contexts. Originality/value – To date, this is among the first studies, to the best of the authors’ knowledge, to investigate cooperative affordable housing with the help of innovative Islamic finance tools in the context of Pakistan. Furthermore, insufficient attention has been given to the enabling and hindering factors behind the acceptance of a framework that seeks to initiate a cooperative scheme based on an innovative waqf financing tool that generates revenue from common areas around a condominium.